2015
DOI: 10.1186/s12864-015-1284-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic diversity of influenza A viruses using next-generation DNA sequencing

Abstract: BackgroundInfluenza viruses exist as a large group of closely related viral genomes, also called quasispecies. The composition of this influenza viral quasispecies can be determined by an accurate and sensitive sequencing technique and data analysis pipeline. We compared the suitability of two benchtop next-generation sequencers for whole genome influenza A quasispecies analysis: the Illumina MiSeq sequencing-by-synthesis and the Ion Torrent PGM semiconductor sequencing technique.ResultsWe first compared the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
103
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 79 publications
2
103
0
Order By: Relevance
“…Higher error rates have been observed with the Ion Torrent PGM than with the Illumina MiSeq, highlighting the importance of the error model in distin- guishing variants from error (38). Similar to other studies, we found that sequencing errors were more often insertions and deletions and primarily located in homopolymer regions (38,39).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Higher error rates have been observed with the Ion Torrent PGM than with the Illumina MiSeq, highlighting the importance of the error model in distin- guishing variants from error (38). Similar to other studies, we found that sequencing errors were more often insertions and deletions and primarily located in homopolymer regions (38,39).…”
Section: Discussionsupporting
confidence: 76%
“…Higher error rates have been observed with the Ion Torrent PGM than with the Illumina MiSeq, highlighting the importance of the error model in distin- guishing variants from error (38). Similar to other studies, we found that sequencing errors were more often insertions and deletions and primarily located in homopolymer regions (38,39). While the use of long-range, inverse PCR specifically enriched samples for virus with intact genomes, fragmented genomes would not have amplified and, ultimately, were not evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the known error rate of the Illumina sequencing platform (36, 37) and the stringency of these variant call criteria, we used a minimum allele frequency cutoff of 1% to identify variants. Each of the identified variants was visually inspected and excluded if the variant was supported by <10 reads (38) or if the average read position of the variant occurred outside the middle 50% of the short read (35). We made one exception to these variant processing protocols.…”
Section: Methodsmentioning
confidence: 99%
“…[3436] Furthermore, the low error rate for Illumina minimizes base call errors in the primer tags that could lead to the creation of artificial variants and distort quasispecies distributions. [33, 48] Thus, SVS allowed us to determine viral variants and quasispecies population with high accuracy and sensitivity. We note that errors from first-strand DNA synthesis during reverse transcription could not be corrected using SVS.…”
Section: Discussionmentioning
confidence: 99%